2017
DOI: 10.3892/mmr.2017.6827
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-661 promotes non-small cell lung cancer progression by directly targeting RUNX3

Abstract: Lung cancer is the primary cause of cancer‑associated mortality in men and women worldwide. Increasing evidence indicates that abnormal microRNA (miRNA) expression contributes to the carcinogenesis and progression of multiple human cancers, including non‑small cell lung cancer (NSCLC). Therefore, miRNAs exhibit the potential to act as biomarkers for the diagnosis, treatment and prognosis of human malignancies. miRNA‑661 (miR‑661) has previously been demonstrated to be important in the development of various hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…e current results indicate that the miR495-UBE2C-ABCG2/ERCC1 axis reverses cisplatin resistance by downregulating drug resistance genes in cisplatin-resistant NSCLC cells [22]. e present results also indicate that miR-661 plays an oncogenic role in NSCLC by directly targeting RUNX3, thus indicating that miR-661 can be used to develop new therapies for patients with NSCLC [72]. An increasing number of studies have shown that miRNAs could be used not only as specific biomarkers of cancer (diagnostic biomarkers) but also as dynamic markers of tumor status before (prognostic biomarkers) and during treatment (predictive biomarkers) [73].…”
Section: Ncrnas In Lungsupporting
confidence: 55%
“…e current results indicate that the miR495-UBE2C-ABCG2/ERCC1 axis reverses cisplatin resistance by downregulating drug resistance genes in cisplatin-resistant NSCLC cells [22]. e present results also indicate that miR-661 plays an oncogenic role in NSCLC by directly targeting RUNX3, thus indicating that miR-661 can be used to develop new therapies for patients with NSCLC [72]. An increasing number of studies have shown that miRNAs could be used not only as specific biomarkers of cancer (diagnostic biomarkers) but also as dynamic markers of tumor status before (prognostic biomarkers) and during treatment (predictive biomarkers) [73].…”
Section: Ncrnas In Lungsupporting
confidence: 55%
“…The collection of patients and specimens was similar with the method described previously 32,33 . Fifty-two paired human cervical cancer (CC) and adjacent nontumor cervical tissues were collected from the Tongji Hospital Affiliated with the Tongji Medical College of Huazhong University of Science and Technology (HUST) between January 2018 and December 2018.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, luciferase reporter assay was performed described previously 33 . The cells were cultured in 24-well plates and cotransfected with the wt or mt Sema4C 3′-UTR vector together with 50 nM miR-31-3p mimics or NC miRNA with Lipofectamine 2000 Reagent (Thermo Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…Based on the above research, we speculated that miR-486-5p expression level might be declined in regulation of the progression of NSCLC. Additionally, targeted genes such as NOB1 ( 19 ), RUNX3 ( 20 ) and FOXM1 ( 21 ) have been found to influence the tumorigenesis of NSCLC. Nonetheless, the role of GAB2 in NSCLC is rarely reported.…”
Section: Introductionmentioning
confidence: 99%